Gender effect on cardiac involvement in myotonic dystrophy type 1. (25th December 2020) - Garibaldi, Matteo; Lauletta, Antonio; Bucci, Elisabetta; Fionda, Laura; Vanoli, Fiammetta; Leonardi, Luca; Alfieri, Girolamo; Tufano, Laura; Morino, Stefania; Merlonghi, Gioia; Anibaldi, Paolo; Salvetti, Marco; et al.
Abstract: Background and purpose: Cardiac involvement is observed in about 80% of subjects with myotonic dystrophy type 1 (DM1) and is mainly characterized by cardiac conduction and/or rhythm abnormalities (CCRAs), possibly leading to sudden cardiac death (SCD). Our objective was to investigate whether the gender difference may influence the cardiac involvement and SCD in DM1. Methods: We analyzed prevalence and incidence of cardiological abnormalities in males versus females in 151 consecutive DM1 patients over a 35‐year follow‐up period. Results: Fifty‐five patients, 35 males (62.5%) and 20 females (42.5%), developed some type of CCRA during the follow‐up period (mean 7.82 ± 6.21 years). CCRA overall, and specifically cardiac conduction abnormalities (CCAs), were significantly more frequent in males than in females ( p = 0.043 and p = 0.031, respectively). CCRAs progressed in 16 males (45.7%) and six females (30%). Twenty‐four patients, 14 males (25.0%) and 10 females (21.3%), died during the follow‐up. Nine of them, six males (10.7%) and three females (6.4%), had SCD. After correction for Muscular Impairment Rating Scale progression, cytosine thymine‐guanine expansion, and follow‐up duration, a higher prevalence of CCAs was independently associated with male gender ( p = 0.039), but independent association with gender was not detected for CCRAs overall, cardiac rhythm abnormalities, and SCD prevalence, even if prevalence was higher in males than females. Conclusions: The overall risk of occurrence of CCAs in DM1 is significantly higher in males than females regardless of genetic background and disease severity and progression. Moreover, the data also suggest a similar impact for male gender for CCRAs overall, CCAs, and SCD even if not statistically significant. Abstract : The overall risk of cardiac abnormalities in myotonic dystrophy type 1 is significantly higher in males regardless of genetic background and disease severity and progression.